2018
DOI: 10.1039/c7cp07656h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical characterization of sulfur-to-selenium substitution in an emissive RNA alphabet: impact on H-bonding potential and photophysical properties

Abstract: We employ density functional theory (DFT) and time-dependent DFT (TDDFT) calculations to investigate the structural, energetic and optical properties of a new computationally designed RNA alphabet, where the nucleobases, A,G, C, andU (ts-bases), have been derived by replacing sulfur with selenium in the previously reported tz-bases, based on the isothiazolo[4,3-d]pyrimidine heterocycle core. We find out that the modeled non-natural bases have minimal impact on the geometry and energetics of the classical Watso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 72 publications
2
20
0
1
Order By: Relevance
“…Theoretical characterization of the impact of sulfur-toselenium substitution on hydrogen-bonding potential and photophysical properties in an emissive RNA alphabet has shown that the replacement of sulfur with selenium in derived nucleobases has a minimal effect on the geometries and energies of base pairs in the classical Watson-Crick model, while base pairs in the Hoogsteen model are destabilized, compared with natural pairs (Chawla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical characterization of the impact of sulfur-toselenium substitution on hydrogen-bonding potential and photophysical properties in an emissive RNA alphabet has shown that the replacement of sulfur with selenium in derived nucleobases has a minimal effect on the geometries and energies of base pairs in the classical Watson-Crick model, while base pairs in the Hoogsteen model are destabilized, compared with natural pairs (Chawla et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the structural, energetic, bonding aspects, and optical properties of the th‐bases were theoretically investigated by Samanta et al and Gedik et al Similarly, the electronic structure and optical properties of the tz‐bases were theoretically investigated by Valverde et al, Chawla et al and the current group . In addition, the sulfur‐to‐selenium substitution effects on H‐bonding potential and photophysical properties of the tz‐bases were also theoretically examined by Chawla et al…”
Section: Introductionmentioning
confidence: 99%
“…Recent progresses include a tricyclic cytidine analogue with turn‐on response to duplex formation, a novel quadracyclic adenosine FRET pair, a versatile and exceptionally bright fluorescent pentacyclic adenine analog, an emissive interbase FRET pair, and the emissive isomorphic RNA alphabets (th‐bases and tz‐bases) . Notably, the isomorphic th‐bases and tz‐bases synthesized by Tor's group have gained much attention . For instance, the structural, energetic, bonding aspects, and optical properties of the th‐bases were theoretically investigated by Samanta et al and Gedik et al Similarly, the electronic structure and optical properties of the tz‐bases were theoretically investigated by Valverde et al, Chawla et al and the current group .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations